Frequent in-migration and highly focal transmission of dengue viruses among children in Kamphaeng Phet, Thailand. - Maia A Rabaa; Chonticha Klungthong; In-Kyu Yoon; Edward C Holmes; Piyawan Chinnawirotpisan; Butsaya Thaisomboonsuk; Anon Srikiatkhachorn; Alan L Rothman; Darunee Tannitisupawong; Jared Aldstadt; Ananda Nisalak; Mammen P Mammen; et al. (Public Library of Science (PLoS), 2013)
Revealing the patterns and determinants of the spread of dengue virus (DENV) at local scales is central to understanding the epidemiology and evolution of this major human pathogen. We performed a phylogenetic analysis of the envelope (E) genes of DENV-1, -2, -3, and -4 isolates (involving 97, 23, 5, and 74 newly collected sequences, respectively) sampled from school-based cohort and village-based cluster studies in Kamphaeng Phet, Thailand, between 2004 and 2007. With these data, we sought to describe the spatial and temporal patterns of DENV spread within a rural population where a future vaccine efficacy trial is planned. Our analysis revealed considerable genetic diversity within the study population, with multiple lineages within each serotype circulating for various lengths of time during the study period. These results suggest that DENV is frequently introduced into both semi-urban and rural areas in Kamphaeng Phet from other populations. In contrast, the persistence of viral lineages across sampling years was observed less frequently. Analysis of phylogenetic clustering indicated that DENV transmission was highly spatially and temporally focal, and that it occurred in homes rather than at school. Overall, the strength of temporal clustering suggests that seasonal bottlenecks in local DENV populations facilitate the invasion and establishment of viruses from outside of the study area, in turn reducing the extent of lineage persistence.